Low power emerging wireless technologies - Mahmoudi, Reza; Iniewski, Krzysztof, 1960- (Devices, circuits, and systems., 2013)
Advanced concepts for wireless communications offer a vision of technology that is embedded in our surroundings and practically invisible, but present whenever required. Although the use of deep submicron CMOS processes allows for an unprecedented degree of scaling in digital circuitry, it complicates the implementation and integration of traditional RF circuits. The requirement for long operating life under limited energy supply also poses severe design constraints, particularly in critical applications in commerce, healthcare, and security. These challenges call for innovative design solu.